The impact of interventions in the built environment on physical activity levels: a systematic umbrella review - Yufang Zhang; Marijke Koene; Sijmen A. Reijneveld; Jolanda Tuinstra; Manda Broekhuis; Stefan van der Spek; Cor Wagenaar (BMC, 2022)
Abstract Physical activity is good for people's health. The relationship between the built environment and physical activity has been well documented. However, evidence is both scarce and scattered on specific urban interventions, i.e., intentional redesigns of the built environment that promote physical activity accompanied by pre- and post-effect measurement. This umbrella review aims to synthesize the findings of systematic reviews focused on these urban interventions. We followed the PRISMA 2020 and JBI umbrella review protocol guidelines and searched seven databases covering the period between Jan 2010 and April 2022 using keywords relating to the built environment, health, physical activity, and interventions. This yielded seven systematic reviews, in which we identified several urban interventions that can promote physical activity. We found positive effects of urban interventions on physical activity regarding park renovations, adding exercise equipment, introducing a (new) pocket park, improving cycling environments, improving walking & cycling environments, as well as multi-component initiatives for active travel and enhancing the availability & accessibility of destinations. The findings suggest that the urban environment can effectively promote physical activity, especially by adding various facilities and destinations and by making the environment better suitable for active use.